The Development of E-Modules Project Based Learning for Students of Computer and Basic Networks at Vocational School - Rahayu, Ismi; Sukardi, Sukardi (Universitas Pendidikan Ganesha, 2020)
In the learning process, the teacher acts as the teacher center by using conventional methods so that it causes students to pay less attention to the teacher, and sometimes students experience boredom in learning. The purpose of this research is to develop project-based learning media for computer-based electronic modules and networks. This study uses the Research and Development (R&D) method with 4-D development procedures which include Define, Design, Develop, Desseminate. The data analysis technique uses descriptive analysis techniques to describe the value of the validity, practicality, and effectiveness of the project-based learning E-module. The results of this development research are: the validity of the E-module based on project-based learning is declared valid with the value category 0.83> 0.61, the E-module practicality is based on the responses of two teachers with an average score of 89.3 in the very practical category and 36 student response with an average score of 85.03 in the very practical category. The effectiveness of e-module project-based learning is stated to be effective in improving learning outcomes. Based on the research results, it can be concluded that E-module learning based on project-based learning is valid, practical, and effective to be used as a learning medium in basic computer and network subjects.